THE POLITICAL VISION OF THE ORGANIZATION OF TURKIC STATES: AN ANALYSIS OF THE TURKIC WORLD VISION 2040 - YALDIZ, F. (Eurasian Research Institute, 2023)
After 1991, the phenomenon of the Turkic world turned from an ideological dream to a political reality, with the independent Turkic states becoming equal and sovereign subjects in the international system and international politics. In this process, many cooperation organizations (TURKSOY, TURKPA, TWESCO, etc.) were established among the Turkic states. The Organization of Turkic States (OTS), established in 2009 as the umbrella organization of the Turkic world cooperation organizations, became even stronger with the membership of Uzbekistan in 2019. The 2021 Istanbul Summit and 2022 Samarkand Summit of the OTS are extremely important for the future of cooperation in the Turkic world. In this study, the political vision for the OTS and the Turkic World Vision - 2040 will be analyzed.
Keywords: Istanbul Summit; OTS; Turkic States; Turkic World; Turkic World Vision – 2040